Ringkøbing-Skjern energy atlas for analysis of heat saving potentials in building stock. (1st September 2016) - Petrović, Stefan; Karlsson, Kenneth
Abstract: Ringkøbing-Skjern municipality aims to be 100% self-sufficient in renewable energy supply starting from 2020. It is expected that the building sector will contribute by reducing energy demand by 25–50%. Technical, economic, environmental and geographical aspects need to be considered when analysing such drastic change of municipality's energy system. For that purpose, GIS-based Ringkøbing-Skjern Energy Atlas has been developed. The present paper utilises Ringkøbing-Skjern Energy Atlas together with the Heating Model to calculate potentials and costs of heat saving measures. The results show that the reduction of heating demand by 25% and 35% can be achieved at the annuitized full cost lower than 1.7 and 2 DKK/kWh, respectively. The results also show that significant heat saving potential lies in farmhouses and detached houses as well as in buildings built before 1950. Over 75% of very cheap heat saving potential can be harvested by insulating floors, while majority of heat saving potential cheaper than 2 DKK/kWh can be utilised by insulating floors and installing mechanical ventilation systems. After heat savings and heat supply options are compared from a private-economic perspective, it is concluded that heat savings should be directed towards buildings supplied by oil boilers, natural gas boilers and ground-source heat pumps. Highlights: Ringkøbing-Skjern plans to become self-sufficient in renewable energy supply by 2020. Highly-detailed GIS-based energy atlas is used to analyse potentials for heat savings. Reduction of heating demand by 25% can be achieved for less than 1.7 DKK/kWh. The biggest part of heat saving potential is found around biggest towns. Heat savings should be done in buildings supplied from oil and natural gas boilers.